(untitled) (Washington, D.C., 1981)
The Food Chemicals Codex is the accepted standard for defining the quality and purity of food chemicals. It is frequently referenced by the U.S. Food and Drug Administration and international food regulatory authorities. This "First Supplement to the Fifth Edition" provides revisions and updates, and reports on changes in tests, monographs, and assays to the Fifth Edition. This supplement features initial information that will benefit producers and users of food chemicals, including processed food manufacturers, food technologists, quality control chemists, research investigators, teachers, students, and those involved in the technical aspects of food safety.
Keywords: Food additives,Food additives,Chất phụ gia thực phẩm,Chất phụ gia thực phẩm; Standards,Analysis,Tiêu chuẩn,Phân tích; United States,Hoa Kỳ